Skin prick test in patients with chronic allergic skin disorders - Pooja Bains; Alka Dogra (Wolters Kluwer Medknow Publications, 2015)
Background: Chronic allergic skin disorders are the inflammatory and proliferative conditions in which both genetic and environmental factors play important roles. Chronic idiopathic urticaria (CIU) and atopic dermatitis (AD) are among the most common chronic allergic skin disorders. These can be provoked by various food and aeroallergens. Skin prick tests (SPTs) represent the cheapest and most effective method to diagnose type I hypersensitivity. Positive skin tests with a history suggestive of clinical sensitivity strongly incriminate the allergen as a contributor to the disease process. Aim s and Objectives: To determine the incidence of positive SPT in patients with chronic allergic skin disorders and to identify the various allergens implicated in positive SPT. Methods: Fifty patients of chronic allergic disorders were recruited in this study. They were evaluated by SPT with both food and aeroallergens. Results: In our study, SPT positivity in patients of CIU was 63.41% and in AD was 77.78%. Out of the 41 patients of CIU, the most common allergen groups showing SPT positivity were dust and pollen, each comprising 26.83% patients. SPT reaction was positive with food items (21.6%), insects (17.07%), fungus (12.20%), and Dermatophagoides farinae, that is, house dust mite (HDM) (7.32%). The allergen which showed maximum positivity was grain dust wheat (19.51%). Among nine patients of AD, maximum SPT positivity was seen with Dermatophagoides farinae, pollen Amaranthus spinosus, grain dust wheat, and cotton mill dust; each comprising 22.22% of patients. Conclusion: Our study showed that a significant number of patients of CIU and AD showed sensitivity to dust, pollen, insects, Dermatophagoides farinae, and fungi on SPT. Thus, it is an important tool in the diagnosis of CIU and AD.